Spatial and temporal distributions of live salt-marsh foraminifera in southern New Jersey: implications for sea-level studies - Walker, Jennifer S. (2023)
Geological reconstructions of relative sea-level change have been greatly enhanced by continuous high-resolution records with the use of salt-marsh foraminifera due to their relationship with tidal level in modern environments and subsequent preservation of tests in sediments. A detailed understanding of how live foraminifera assemblages compare to dead or total (live + dead) assemblages and the influence of environmental variables on foraminiferal distributions is essential for their use as a proxy to reconstruct sea level. Here, we evaluated small-scale spatial and temporal (seasonal and interannual) variability of live foraminifera assemblages from four high marsh monitoring stations along a salinity gradient in southern New Jersey over three years. In addition, we measured porewater and sedimentary variables and stable carbon isotopes during each sampling period every three months. In the 184 samples, we identified 11 live agglutinated foraminifera species and four distinct clusters of live foraminifera that correspond to the stations from which they were sampled and to the dead and total assemblages. We found no clear correlation over time between variability in live assemblages and measured environmental variables; however, elevation was the primary controlling factor influencing foraminiferal distributions, with secondary influences from salinity and substrate. The consistency of foraminiferal assemblages on spatial and temporal scales and among live, dead, and total assemblages further reinforces the value of salt-marsh foraminifera as reliable sealevel indicators.